Effects of Hole Perpendicularity Error on Load Distribution in Single-Lap Double-Bolt Composite Joints - LI, Rupeng; XIAO, Ruiheng; GE, Ende; GAO, Hang; BAO, Yongjie; LIU, Xueshu (Engineering Transactions, 2018)
Although automated machines are widely used in composite structure manufacturing, manually drilled holes are usually necessary due to spatial constrains and holes with perpendicularity errors are occasionally generated as a result. Considering the anisotropic properties of composite material, the influences of hole perpendicularity error on mechanical performances of composite joints are different from those of isotropic material. In this study, the effects of hole perpendicularity error on load distribution in single-lap double-bolt composite joints are discussed. A finite element model is first developed and verified both by analytical and experimental results. Parametric studies are then carried out taking into consideration bolt torque and hole perpendicularity error, represented by hole tilting direction and tilting angle. It is found that the hole tilting direction significantly affects on load distribution in composite joints. Although the loads taken by bolts are not significantly affected, it may make one composite plate take more than 60% of total loads. In addition, the influences of tilting angle on load distribution can be ignored in most cases, and as for the bolt torque, it is to enhance the influence of hole tilting direction.